Analytical Challenges in Novel Pentavalent Meningococcal Conjugate Vaccine (A, C, Y, W, X) - Pankaj Sharma; Sameer Kale; Swapnil Phugare; Sunil Kumar Goel; Sunil Gairola (Vaccines)
Multivalent meningococcal conjugate vaccines are a significant focus for the scientific community in light of the WHO’s mission to defeat meningitidis by 2030. Well-known meningococcal vaccines such as MenAfriVac, Nimenrix, Menveo, and MenQuadfi are licensed in various parts of the world and have been successful. Recently, the World Health Organization (WHO) qualified MenFive (meningococcal A, C, Y, W, and X) conjugate vaccine, further enhancing the battery of vaccines against meningitis. The antigenic nature of the current and new serogroups, the selection of carrier proteins, and the optimal formulation of these biomolecules are pivotal parameters for determining whether a biological preparation qualifies as a vaccine candidate. Creating appropriate quality control analytical tools for a complex biological formulation is challenging. A scoping review aims to identify the main challenges and gaps in analyzing multivalent vaccines, especially in the case of novel serogroups, such as X, as the limited literature addresses these analytical challenges. In summary, the similarities in polysaccharide backbones between meningococcal serogroups (C, Y, W sharing a sialic acid backbone and A, X sharing a phosphorous backbone) along with various conjugation chemistries (such as CNBr activation, reductive amination, CDAP, CPIP, thioether bond formation, N-hydroxy succinimide activation, and carbodiimide-mediated coupling) resulting into a wide variety of polysaccharide -protein conjugates. The challenge in analyzing carrier proteins used in conjugation (such as diphtheria toxoid, tetanus toxoid, CRM diphtheria protein, and recombinant CRM) is assessing their purity (whether they are monomeric or polymeric in nature as well as their polydispersity). Additional analytical challenges include the impact of excipients, potential interference from serogroups, selection and establishment of standards, age-dependent behavior of biomolecules indicated by molecular size distributions, and process-driven variations. This article explains the analytical insights gained (polysaccharide content, free saccharide, free proteins, MSD) during the development of the MenFive vaccine and highlights the crucial gaps and challenges in testing.